Behavioral and neural inhibitory control moderates the effects of reward sensitivity on adolescent substance use. (October 2016) - Kim-Spoon, Jungmeen; Deater-Deckard, Kirby; Holmes, Christopher; Lee, Jacob; Chiu, Pearl; King-Casas, Brooks
Abstract: The developmental period of adolescence is characterized by increasing incidence of health risk behaviors, including experimenting with drugs and alcohol. We examined how inhibitory control interacts with reward and punishment sensitivity to predict substance use severity and age of onset among early adolescents. The sample was comprised of 157 early adolescents (13–14 years of age, 52% male). Composite scores for behavioral activation system (BAS), behavioral inhibition system (BIS), and substance use severity and onset were computed using adolescents' questionnaire data, and inhibitory control was assessed based on adolescents' behavioral performance and brain imaging during the Multiple Source Interference Task (MSIT). Structural equation modeling analyses indicated that for both behavioral performance and neural activity indicators of inhibitory control, high levels of BAS predicted earlier onset of substance use among adolescents with low inhibitory control—but not among adolescents with high inhibitory control. BIS was not related to substance use severity and onset among adolescents. The results support the theoretically hypothesized moderating role of inhibitory control and its associated frontal cortex functioning, and offer new insights into the identification of adolescents with neurobehavioral vulnerabilities to developing maladaptive substance use behaviors. Highlights: We study two systems of adolescent risk taking: a reactivity system represented by reward and punishment sensitivity and a cognitive regulation system represented by inhibitory control involving frontal cortex functioning. Our structural equation modeling analyses suggest that inhibitory control, measured by behavioral and neural indicators, moderates the link between reward sensitivity and substance use onset among early adolescents. High behavioral activation system (BAS) is related to early onset among adolescents with low cognitive control but not adolescents with high cognitive control. Substance use may result from heightened reward sensitivity in adolescence; yet, inhibitory control may be targeted for early prevention strategies for regulating reward sensitivity, resulting in a delay in substance use initiation.